Odwrócony uchyłek Meckla u wcześniaka powodujący przejściową niedrożność jelita - Zając, Andrzej; Pawlik, Dorota; Radziszewska, Renata; Katarzyna, Lorenc; Szczepański, Wojciech; Tomasik, Przemysław; Górecki, Wojciech; Lauterbach, Ryszard (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Although Meckel diverticulum morbidity is well known in children and adults, complications appearing in newborns seem to be very rare. Authors present extremely rare case of inverted Meckel diverticulum in premature, causing intermittent bowel obstruction complicated by necrotizing enterocolitis. After three episodes of incomplete bowel obstruction patient died at the age of 65 days with symptoms of ileus, complicated by septicemia and multiorgan dysfunction syndrome. Postmortem examination revealed inverted Meckel diverticulum obliterating small intestine.